The development of a new analytical model for the identification of saccharide binders in paint samples. - Anna Lluveras-Tenorio; Joy Mazurek; Annalaura Restivo; Maria Perla Colombini; Ilaria Bonaduce (PLoS ONE, 2012)
This paper describes a method for reliably identifying saccharide materials in paintings. Since the 3(rd) millennium B.C., polysaccharide materials such as plant gums, sugar, flour, and honey were used as binding media and sizing agents in paintings, illuminated manuscripts, and polychrome objects. Although it has been reported that plant gums have a stable composition, their identification in paint samples is often doubtful and rarely discussed. Our research was carried out independently at two different laboratories: the Getty Conservation Institute in Los Angeles, USA (GCI) and the Department of Chemistry and Industrial Chemistry of the University of Pisa, Italy (DCCI). It was shown in a previous stage of this research that the two methods give highly comparable data when analysing both reference paint samples and paint layers from art objects, thus the combined data was used to build a large database. In this study, the simultaneous presence of proteinaceous binders and pigments in fresh and artificially aged paint replicas was investigated, and it highlighted how these can affect the sugar profile of arabic, tragacanth, and fruit tree gums. The environmental contamination due to sugars from various plant tissues is also discussed. The results allowed the development of a new model for the reliable identification of saccharide binders in paintings based on the evaluation of markers that are stable to ageing and unaffected by pigments. This new model was applied to the sugar profiles obtained from the analysis of a large number of samples from murals, easel paintings, manuscripts, and polychrome objects from different geographical areas and dating from the 13(th) century BC to the 20(th) century AD, thus demonstrating its reliability.